The Effect of Hypertension Duration and the Age of Onset on CV Risk Factors Expression in Perimenopausal Women - Ljiljana Trtica Majnarić; Ivo Martinović; Šefket Šabanović; Stjepan Rudan; František Babič; Thomas Wittlinger (International Journal of Hypertension)
Background. The impact of hypertension duration and the time of onset on the expression of metabolic syndrome (MS) and other CV risk factors, in perimenopausal women, have not been studied so far. Methods. A total of 202 women, old 47–59 years, and diagnosed with hypertension, were recruited from primary care practices in eastern Croatia. The categories of hypertension duration were defined as <5, 5–10, and >10 years. Data were analyzed by standard statistical procedures. Results. The proportion of women with MS increases in parallel with hypertension duration (p = 0.025). Among the examined CV risk factors, significant increase in parallel with hypertension duration was found for body mass index (p = 0.007) and triglycerides (p = 0.07). The highest proportion of women with diabetes duration of less than 5 years, indicating recent diabetes onset, was found in the category of hypertension duration of less than 5 years, corresponding with the onset of hypertension in the time around menopause (p = 0.003). The strongest linear correlations with BMI and waist circumference were found for total serum cholesterol (r = 0.355 and 0.499, respectively). Conclusion. Hypertension onset at the time around menopause appears together with abdominal obesity and may be a driving force for CV risk factor accumulation in postmenopausal women.